s11_mthsc208_hw07

s11_mthsc208_hw07 - MthSc 208, Spring 2011 (Differential...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: MthSc 208, Spring 2011 (Differential Equations) Dr. Macauley HW 7 Due Friday February 18th, 2011 (1) Sove the following initial value problems. (a) y - y - 2y = 0, y(0) = -1, y (0) = 2 (b) y - 4y - 5y = 0, y(1) = -1, y (1) = -1 (c) y + 25y = 3, y(0) = 1, y (0) = -1 (d) y - 2y + 17y = 0, y(0) = -2, y (0) = 3 (2) Find the general solution to the following 2nd order linear inhomogeneous ODEs, by solving the associated homogeneous equation, and then finding a constant (particular) solution. (a) y + y - 12y = 24 (b) y = -4y + 3 (3) As we've seen, to solve ODE of the form y + py + qy = 0 , p and q constants rt we assume that the solution has the form e , and then we plug this back into the ODE to get the characteristic equation: r2 +pr +q = 0. Given that this equation has a double root r = r1 (i.e., the roots are r1 = r2 ), show by direct substitution that y = tert is a solution of the ODE, and then write down the general solution. [Hint: If there's a double-root, then it must be - p . Why?] 2 (4) Suppose that z(t) = x(t) + iy(t) is a solution of z + pz + qz = Aeit . Substitute z(t) into this equation above. Then compare (equate) the real and imaginary parts of each side to prove two facts: x + px + qx = A cos t y + py + qy = A sin t . Write a sentence or two summarizing the significance of this result. (5) Solve the following initial value problems using the method of undetermined coefficients. (a) y + 3y + 2y = -3e-4t , y(0) = 1, y (0) = 0 (b) y + 2y + 2y = 2 cos 2t, y(0) = -2, y (0) = 0 (c) y + 4y + 4y = 4 - t, y(0) = -1, y (0) = 0 (d) y - 2y + y = t3 , y(0) = 1, y (0) = 0 (6) Solve the following first order differential equations using the method of undetermined coefficients. (a) y - 3y = 5e2t (b) y + 2y = 3t (c) T = k(-t - T ) (d) T = k(A sin t - T ) ...
View Full Document

Ask a homework question - tutors are online